Reptilase-Induced Shortening of Coagulation Times in Normal and Hemophilic Individuals - Harder, A. J; Stadelmann, H; Straub, P. W (Thrombosis and Haemostasis, 1972)
In 5 normal volunteers infusion of small doses of Reptilase-def., a thrombin-like snake venom enzyme of Bothrops atrox, led to a transient shortening of the clotting time, which was significant when compared with a control group infused with glucose. In hemophilic individuals, clotting and recalcification times were also considerably shortened, the maximal effect in both groups occurring simultaneously with cryoprecipitability and positive paracoagulation phenomena. Whether this accelerating effect on blood coagulation is mediated by circulating soluble fibrin complexes, is not yet established. However, the clot-promoting action of Reptilase must predominantly be localized at the level of fibrinogen/fibrin conversion rather than in earlier phases of coagulation.